Dampak Literasi Keuangan, Gaya Hidup Hedonis, dan Locus of Control Terhadap Perilaku Keuangan Mahasiswa Universitas Lambung Mangkurat - Putrie, Rizky Maharani; Ratumbuysang, Monry Fraick Nicky Gillian; Rizky, Maulana; Setiawan, Ananda (Universitas Negeri Surabaya, 2024)
This research aims to analyze the impact of Financial Literacy, Hedonic Lifestyle, and Locus of Control on the Financial Behavior of Lambung Mangkurat University Students. This problem focuses on the low level of financial literacy among students, which is exacerbated by a hedonistic lifestyle culture. As a result, students have a low locus of control, which causes less wise financial behavior. Data was collected through observation and questionnaires, then analyzed using a quantitative descriptive approach. The subjects of this research were students at Lambung Mangkurat University. The research with a sample of 260 respondents. The analysis tool used is Structural Equation Modeling (SEM) with SmartPLS version 3.0 software. The research results show that there is a positive impact between Financial Literacy, Hedonic Lifestyle, and Locus of Control on the Financial Behavior of Lambung Mangkurat University Students.